DOP34 Long-term outcome of Acute Severe Ulcerative Colitis responsive to intravenous steroid: A multicenter study of the Italian Group for the study of Inflammatory Bowel Disease (IG-IBD). (27th May 2021) - Festa, S; Scribano, M L; Aratari, A; Bezzio, C; Principi, M; Pugliese, D; Ribaldone, D G; Furfaro, F; Mocci, G; Spagnuolo, R; Vernia, P; Costa, F; et al.
Abstract: Background: The appropriate maintenance treatment for patients with acute severe ulcerative colitis (ASUC) responsive to intravenous steroids (IVS) is still a matter of debate. Although major Guidelines consider thiopurine maintenance an option in this setting, the long-term benefit of early immunomodulator (IMMs) initiation is not well established. The aim of our study was to explore the long-term outcome of patients with ASUC responsive to IVS who received different maintenance strategies Methods: In a multicenter retrospective study, all patients with ASUC hospitalized between January 2005 and December 2017 in 14 Italian IBD referral centres were reviewed. Thiopurine and biologic-naïve patients experiencing their first acute severe attack and who responded to IVS were included in the study. Maintenance treatment was prescribed by attending physicians according to their clinical judgment. The main outcomes were recurrent flares requiring escalation of therapy, new hospitalization, and long-term colectomy rate. The Kaplan-Meier survival method was used to estimate the cumulative probability of a course without the main outcomes. Differences between curves were tested using the log-rank test. A propensity score matching analysis was performed to establish comparable groups of patients who received different maintenance treatment Results: Overall 372 patients were reviewed. Of these, 141 met the inclusion criteria (males 61.7%, median age 34.5 (IQR 23–50). After response to IVS, 82 patients (58.1%) received maintenance treatment with aminosalicylates, 42 (29.8%) received IMMs and 17 (12.1%) were maintained with scheduled infliximab (IFX) + thiopurines. After a median follow-up of 48 (IQR 25–90) months, 94 patients (68.8%) experienced a flare requiring escalation of therapy, 51 (36.1%) required new hospitalization and 18 (12.8%) underwent colectomy. After 12, 36 and 60 months after the acute attack, the cumulative probability of a course without escalation of therapy was 59.6%, 33.3% and 23.1%; the cumulative probability of a hospitalization-free course was 83.9%, 67.4% and 59.5%; the cumulative probability of a colectomy-free course was 96.3%, 90.2%, and 88.9%. No differences were observed between patients receiving aminosalicylates, IMMs or IFX as maintenance treatment (log-rank test: p= 0.39; p = 0.41; p = 0.11 respectively). After a propensity score matching analysis, no significant difference in main outcomes was observed between patients maintained with aminosalicylates or IMMs/IFX Conclusion: IMM-naïve ASUC patients responsive IVS remain at risk of relapse requiring escalation of therapy. Early IMMs introduction after the acute attack did not reduce the risk of escalation of therapy, hospitalization or colectomy